Decent Care for Migrant Households: Policy Alternatives to Sri Lanka's Family Background Report. (10th June 2019) - Withers, Matt
Abstract: Domestic worker migration can profoundly reconfigure unpaid care arrangements within migrant households, often exacerbating gendered inequalities in providing and receiving care. While the International Labor Organization has led rights advocacy around migrant domestic work, there remains a dearth of attention to the relationship between feminized migration and unpaid care. In Sri Lanka, this policy space has been occupied by the Family Background Report: a series of regulations that reinforce maternal caregiving by restricting the migration of women with young children. An alternative "decent care" approach, involving investment in local care infrastructure, could yield multiple benefits while promoting a gender-inclusive decent work agenda.